1999
DOI: 10.1006/viro.1999.9866
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E4 34k and E4 11k Inhibit Double Strand Break Repair and Are Physically Associated with the Cellular DNA-Dependent Protein Kinase

Abstract: The adenovirus oncoproteins E4 34k and E4 11k, the products of E4 open reading frames 6 and 3, respectively, individually prevent the formation of concatemers of the linear viral genome in infected cells. We show here that genome concatenation in E4 mutant-infected cells requires the cellular DNA-dependent protein kinase (DNA PK) and that E4 34k inhibits V(D)J recombination, a normal cellular process that is also dependent on DNA PK. We further show that both E4 34k and E4 11k coimmunoprecipitate with DNA PK. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 33 publications
3
141
0
Order By: Relevance
“…Viral DNA becomes ligated into long concatomers of randomly oriented genomes by the cellular NHEJ proteins (Weiden and Ginsberg, 1994;Boyer J et al, 1999;Evans and Hearing, 2003;Shepard and Ornelles, 2004). Even when NHEJ is blocked by mutations in NHEJ proteins, the MRN Cullin-based ubiquitin ligases and their relationship to the adenovirus E1B-55K/E4orf6 ubiquitin ligase complex.…”
Section: E1b-55k Has Several Activities That Inhibit P53 Functionmentioning
confidence: 99%
“…Viral DNA becomes ligated into long concatomers of randomly oriented genomes by the cellular NHEJ proteins (Weiden and Ginsberg, 1994;Boyer J et al, 1999;Evans and Hearing, 2003;Shepard and Ornelles, 2004). Even when NHEJ is blocked by mutations in NHEJ proteins, the MRN Cullin-based ubiquitin ligases and their relationship to the adenovirus E1B-55K/E4orf6 ubiquitin ligase complex.…”
Section: E1b-55k Has Several Activities That Inhibit P53 Functionmentioning
confidence: 99%
“…It has also been reported that DNA-PK inhibits retrovirus integration 59 and that DNA-PK associated with adenovirus E4 gene products inhibits concatamer formation of the adenovirus genome. 60 Since RNaseL and DNA-PK are universally present in all cell types, it is likely that all cells are able to activate inflammatory cytokine production and mount responses to clear vector nucleic acids. The finding that such universal and primitive responses are involved in anti-viral immunity has significantly broadened our definition of innate immunity and should alter future approaches to modify vector structure and delivery to improve vector performance.…”
Section: Innate Immunitymentioning
confidence: 99%
“…More recent evidence suggests that some of the redundant functions shared by both E4 proteins are linked to their ability to interact with common cellular and viral factors. For example, Ketner and coworkers recently reported Ad5 ORF3 and ORF6 binding to the DNAdependent protein kinase (DNA PK) (Boyer et al, 1999), an essential element involved in controlling the end-joining mechanism in the double-strand break repair (DSBR) system (reviewed in Smith and Jackson, 1999). Functional analyses show that ORF6, although not ORF3, can inhibit V(D)J-joining (Boyer et al, 1999), a process that requires DNA PK.…”
Section: E4 Orf3 and E4 Orf6mentioning
confidence: 99%
“…For example, Ketner and coworkers recently reported Ad5 ORF3 and ORF6 binding to the DNAdependent protein kinase (DNA PK) (Boyer et al, 1999), an essential element involved in controlling the end-joining mechanism in the double-strand break repair (DSBR) system (reviewed in Smith and Jackson, 1999). Functional analyses show that ORF6, although not ORF3, can inhibit V(D)J-joining (Boyer et al, 1999), a process that requires DNA PK. Moreover, Young and coworkers showed that both ORF3 and 6 can inhibit the repair of speci®c double-strand breaks induced by the Saccharomyces cerevisiae HO endonuclease in co-infected cells (Nicola s et al, 2000).…”
Section: E4 Orf3 and E4 Orf6mentioning
confidence: 99%
See 1 more Smart Citation